Revolutionizing Commutes: Unraveling Consumer Citizenship Behavior through Value Co-creation in Public Transportation - Firdaus, Muhammad Iqbal; Lesmini, Lis; Rahman, Nor Aida Abdul (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
The service-dominant logic paradigm underscores the significance of consumer participation in co-creating value. Co-creation serves as a source of competitive advantage for companies, even those oriented towards public services. This study aims to analyze the factors motivating public transportation users to engage in co-creation behavior, intending to foster the development of their citizenship behavior for the benefit of other stakeholders. To address the research questions, an electronic survey was conducted among MRT Jakarta users, employing purposive sampling techniques and successfully gathering 201 valid samples. Partial least square structural equation modeling (PLS-SEM) was employed to test the relationships between variables in the study. The findings indicate that co-creation behavior is influenced by users’ identification with MRT Jakarta brand and their positive attitude. Subsequently, this co-creation behavior motivates users to engage in consumer citizenship behavior, representing going the extra mile. This study encourages service providers to establish more open communication channels between service providers and passengers, including empowering passengers to provide input, suggestions, or even participate in service development programs.